2004
DOI: 10.1182/blood-2003-08-2852
|View full text |Cite
|
Sign up to set email alerts
|

The functional cobalamin (vitamin B12)–intrinsic factor receptor is a novel complex of cubilin and amnionless

Abstract: Introduction Cobalamin (vitamin B 12 ) is a coenzyme for the enzymes of intermediate metabolism, methionine synthase, and methylmalonyl-CoA mutase, and deficiency of the vitamin leads to potentially lethal manifestations such as megaloblastic anemia and severe combined degeneration of the central nervous system. Cobalamin deficiency, which is one of the most common vitamin-deficiency diseases, is most often due to failure at a step in the complicated and highly specific gastrointestinal uptake mechanisms for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
253
2
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 263 publications
(268 citation statements)
references
References 33 publications
(62 reference statements)
10
253
2
3
Order By: Relevance
“…7 Amnionless (AMN), originally identified as a visceral endoderm specific protein essential for embryonic development, is a 50 kDa transmembrane protein expressed in polarized epithelia that binds tightly to the cubilin N-terminal end. 8,9 Mutations in CUBN and AMN account for 54.8% (23/42) and 23.8% (10/42) of IGS, respectively, whereas mutations in other still unidentified genes account for 21% (9/42). 10 More recently, IGS was caused by a compound heterozygous mutation in CUBN comprising a missense mutation in the paternal allele (c.1010 C>T) and a partial gene deletion in the maternal allele.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…7 Amnionless (AMN), originally identified as a visceral endoderm specific protein essential for embryonic development, is a 50 kDa transmembrane protein expressed in polarized epithelia that binds tightly to the cubilin N-terminal end. 8,9 Mutations in CUBN and AMN account for 54.8% (23/42) and 23.8% (10/42) of IGS, respectively, whereas mutations in other still unidentified genes account for 21% (9/42). 10 More recently, IGS was caused by a compound heterozygous mutation in CUBN comprising a missense mutation in the paternal allele (c.1010 C>T) and a partial gene deletion in the maternal allele.…”
Section: Introductionmentioning
confidence: 99%
“…4,5,6 IGS has also been explained as mutations in the cubilin gene (CUBN OMIM # 602997) located on chromosome 10 or in the amnionless gene (AMN OMIM # 605799) located on chromosome 14. [7][8][9][10] These two proteins are parts of the IF-Cbl receptor complex, also called cubam, which is expressed in the ileal mucosa and in the renal proximal tubules. 7,9 Cubilin is a 460 kDa multiple ligand binding protein, which cannot internalize the IF-Cbl complex by itself.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Norway, all the studied cases were due to mutations in the AMN gene, whereas cases from Mediterranean regions had mutations in either the CUBN or the AMN gene . It has been demonstrated that AMN functions in the same pathway as cubilin and forms a complex designated cubam, which is essential for endocytosis/trancytosis of several ligands (Fyfe et al 2004).…”
Section: Introductionmentioning
confidence: 99%